ADOLESCENT GLUTEN INTAKE: POPULATION-BASED STUDY IN A BRAZILIAN CITY - Daniela de Assumpção; Caroline Dario Capitani; Ana Carolina Rocha; Marilisa Berti de Azevedo Barros; Antonio de Azevedo Barros Filho
ABSTRACT Objective: To estimate the prevalence of gluten intake according to demographic, socioeconomic, and health-related behavioral variables in adolescents. Methods: This is a population-based cross-sectional study with a two-stage cluster sampling, conducted in Campinas, São Paulo, in 2008-2009. Foods containing gluten were identified using a 24-hour Recall. We calculated the prevalence and adjusted prevalence ratios with multiple Poisson regression. Results: The study had a sample of 924 adolescents aged 10 to 19 years. Among the foods assessed, 26.9% (confidence interval of 95% - 95%CI 25.3-28.6) contained gluten. We found a higher prevalence of gluten intake in younger individuals (10 to 14 years), as well as in subgroups of adolescents who had a higher number of household appliances, attended school, consumed fewer beans and vegetables during the week (<4 times), and whose head of the family had better education level (≥12 years of schooling). The main food sources of gluten in their diet were: bread, cakes, and cereals (30.2%), chocolate milk (14%), chicken nuggets (12.3%), and cookies (11%). Conclusions: The results of the study show the epidemiological profile associated with gluten intake in adolescents and could support actions aimed at promoting healthy eating habits and preventing gluten-related diseases.